Birth history as a predictor of stunting incidence among toddlers - Sari, Afrina Aulia; Palimbo, Adriana; Ningrum, Novalia Widiya; Salmarini, Desilestia Dwi; Jannah, Raudhatul (Health Sciences International Journal, 2025)
Background: Stunting remains a critical public health challenge in Indonesia, with a national prevalence of 21.6%, reflecting long-term nutritional deprivation and irreversible developmental impairments. Despite lower stunting rates (4.3%) at Pemurus Baru Community Health Center, local disparities persist, necessitating investigation into perinatal determinants like birth weight, length, and gestational age, which may establish biological pathways to stunting. Objective:  This study aimed to analyze the association between adverse birth history and stunting incidence among toddlers aged 12–60 months. Methods: A case-control design was employed, retrospectively comparing 63 stunted children (cases) with 63 non-stunted controls matched by age and location. Data were extracted from perinatal records (2019–2023) and analyzed for birth weight, length, and preterm status. Results: The study revealed significant differences in birth history between stunted and non-stunted toddlers. The case group showed higher prevalence of low birth weight (36.5% vs 12.7%), short birth length (60.3% vs 39.1%), and preterm birth (36.5% vs 14.3%) compared to controls. All three birth parameters demonstrated substantial disparities between groups, with the case group consistently exhibiting worse outcomes across all measured indicators. Conclusion:  Intrauterine growth restriction, maternal malnutrition, and premature delivery are stronger predictors of stunting than postnatal factors alone. Prevention strategies must prioritize early interventions during the first 1,000 days, including prenatal nutritional supplementation and fetal growth monitoring, supported by policy reforms integrating birth history into surveillance systems.